The Effect of Test, Electrode, and Rate on Electrocochleography Measures - Lake, Alyson Butler; Stuart, Andrew (Journal of the American Academy of Audiology, 2019)
Electrocochleography (ECochG) is the measurement of stimulus-related cochlear potentials and the compound action potential (AP). Its primary clinical application is with the assessment of inner ear disorders. There are few studies examining the variability of ECochG measures.The objective of the study was to examine the effect of test (i.e., initial versus retest), electrode (i.e., extratympanic versus tympanic), and stimulus rate (i.e., 7.7 versus 77.7/sec) on ECochG indices (i.e., summating potential [SP] amplitude, AP latency, AP amplitude, SP/AP amplitude ratio, and SP/AP area ratio).Correlational and three-factor repeated measures designs were employed.Eighteen normal-hearing young adults participated.ECochG responses were obtained with 90 dB nHL click stimuli for an initial test and retest at two stimulus rates with a commercially available extratympanic (TIPtrode™) and tympanic (Lilly TM-Wick) electrode. Separate repeated measures linear mixed-model analysis of variance examined the effect of test, electrode, and rate for all ECochG indices. Test–retest variability was also examined with correlation analyses; an examination of mean test–retest differences and their 95% confidence intervals (CI); and construction of Bland-Altman plots.The presence of SP and AP responses varied across experimental conditions. Electrode and rate were statistically significant predictors (p < 0.05) of SP and AP responses: SP and AP responses were more likely to be present with the tympanic electrode and at the slow rate. Statistically significant correlations (p < 0.05) were found between initial tests and retests with all ECochG indices with both electrodes with the exception of SP amplitude with the TIPtrode™ electrode. There were no significant main effects of test (initial versus retest) or interactions of test and electrode or rate for any of the ECochG indices (p > 0.05). The 95% CI of the mean test–retest differences contained 0 confirming that the effect of test was not statistically significant. There was a statistically significant main effect of electrode (p < 0.05) on three ECochG measures. The Lilly TM-Wick electrode produced larger SP amplitudes, AP amplitudes, and SP/AP area ratios than TIPtrode™ electrodes. A statistically significant main effect of rate (p < 0.05) was identified for all ECochG measures. The effect of rate on AP latency and amplitude was expected. Increasing the stimulus rate prolonged the AP latency and decreased AP amplitude. SP amplitude was larger for the faster rate.There was no difference between electrodes with regard to test–retest measures. However, considering the higher likelihood of ECochG SP and AP responses and larger SP amplitude, SP/AP amplitude ratio, and SP/AP area ratio indices, the tympanic electrode placement is recommended for clinical practice. The addition of a fast stimulus rate may be considered for enhanced SP amplitude, SP/AP amplitude ratio, and SP/AP area ratio albeit with the consideration of the loss of SP and AP responses in some individuals.
Keywords: action potential; electrocochleography; electrode; stimulus rate; summating potential; test–retest variability